EFFECT OF OWN CAPITAL, CAPITAL LOAN, TURNOVER SALES, AND USE OF HOURS TO PROFITABILITY (Empirical Study on The Actors SMEs Market Ngarsopuro Surakarta) - Edi Wibowo & Setyaningsih (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
This study aimed to analyze effect of equity capital, debt capital, sales omzet, andutilization of working hours on profitability. This study using the census research with44 respondents were SMEs in Ngarsopuro Market Surakarta. To test our hypothesesusing multiple regression analysis, data processing using SPSS. The results of this studyindicate that (1) equity capital have positive and significant effect on profitability, thushypothesis 1 supported. (2) debt capital have positive and significant effect onprofitability, thus hypothesis 2 supported. (3) sales omzet have positive and significanteffect on profitability, thus hypothesis 3 supported. (4) utilization of working hours havenot significant effect on profitability, thus hypothesis 4 rejected. SMEs in NgarsopuroMarkets Surakarta suggested increasing the efficiency of inventory management,advised to raise working capital through a capital increase itself or seek additionalforeign capital in the form of loans and improve financial and marketing management.Keywords: equity capital, debt capital, sales omzet, utilization of working hours, profitability, SMEs